PENYELESAIAN PENGALIHAN OBJEK JAMINAN FIDUSIA KEPADA PIHAK KETIGA TANPA PERSETUJUAN PENERIMA FIDUSIA DI KOTA SAMARINDA - Mauli Rianda Yusuf; M. Fauzi; Amsari Damanik (Law Department, University of Widya Gama Mahakam Samarinda, 2025)
Background: Fiduciary guarantees are commonly used in financing agreements to strengthen the position of financing company, serving as a guarantee that debtor will fullfill their obligations. However, in implementation of financing agreements, there are still debtors who fail to carry out the terms of agreement. One significant issue is the debtor's transfer of the financed object which is encumbered with a fiduciary guarantee to a third party during the credit period without the creditor's consent, known as a take over. Research Metodes: This study employs a socio-legal research approach which examines and analyzes how law operates within society. Findings: The findings of this research indicate that the transfer of fiduciary collateral to third parties without the consent of the creditor is a recurring problem. Debtors who transfer fiduciary guarantee to a third party without the creditor’s approval are committing a breach of contract, which can result in legal consequences, including the potential for criminal prosecution. Resolution of disputes between a creditor and a debtor regarding a fiduciary guarantee whose object has been transferred to a third party in Samarinda is done through both litigious and non-litigious. Conclusion: Out-of-court dispute resolution is employed creditors, taking into account the existence of the fiduciary collateral and the fulfillment of credit installments. However, if the fiduciary collateral is missing, and the credit installments are not paid, the creditor will file a report with the police, which may result in criminal charges under Article 36 of Law Number 42 of 1999 concerning Fiduciary Guarantee.